A novel method to synthesize stable nitrogen-rich polynitrobenzenes with π-stacking for high-energy-density energetic materials. Issue 73 (24th August 2018) - Yang, Xiaoming; Lin, Xinyu; Yang, Li; Zhang, Tonglai
Abstract : A larger multi-nitro, multi-azide and multi-oxidized furazan ring compound with π–π stacking is herein reported. The coupling reaction of a NN bond and an azido was an efficient method to synthesize benzotriazole. Abstract : Two nitrogen-rich energetic compounds with π-stacking, 1, 1′-dichloro-2, 2′, 3, 3′, 6, 6′-hexanitro-5, 5′-dihydroxyazobenzene (1 ) and 8-(2, 4, 6-triazido-3, 5-dinitrophenyl)-8 H -[1, 2, 3]triazolo[4′, 5′:5, 6]benzo[1, 2- c :3, 4- c ′]bis([1, 2, 5]oxadiazole) 1, 4-dioxide (2 ), were prepared by a novel synthesis method, and their structures were determined by single-crystal X-ray diffraction analysis. The decomposition temperature of 1 is 336 °C and 2 exhibits excellent heat of formation of 1160.5 kJ mol −1 (2.21 kJ g −1 ). The condensation reaction of the coupling of a NN bond and an azido from 1 to 2 was proved to be an efficient method to synthesize benzotriazole. This synthetic strategy for benzotriazole may arouse considerable interest in the area of organic synthesis.